Chemerin alleviates the placental oxidative stress and improves fetal overgrowth of gestational diabetes mellitus mice induced by high fat diet - Xuan Zhou; Yi Jiang; Zizhuo Wang; Lijie Wei; Huiting Zhang; Chenyun Fang; Shenglan Zhu; Yuanyuan Du; Rui Su; Weikun Li; Zhenzhen He; Liangnan Zhang; et al. (BMC, 2024)
Abstract Background Evidence has shown that oxidative stress induced by high glucose microenvironment in placenta of gestational diabetes mellitus (GDM) is indispensable to the progression of this condition. Adipokine chemerin was linked with GDM, yet the roles of chemerin in placental oxidative stress and its underlying effects on GDM in vivo remain elusive. Methods We firstly analyzed the disparities of oxidative stress levels in placenta between GDM and normoglycaemic pregnant women, and then added recombinant active chemerin to the high-glucose treated human trophoblastic cells to investigate effects of chemerin on reactive oxygen species (ROS), total antioxidant capacity (T-AOC) and intake of glucose. Finally, a GDM animal model induced by high-fat diet (HFD) was established and the impacts of chemerin on oxidative stress of placenta and fetal growth of GDM were explored. Results Analysis of human samples showed that the extent of lipid peroxidation in placenta was significantly elevated in GDM patients compared with their normoglycaemic counterparts. In the high glucose cell model, active chemerin lessened the content of ROS, heightened the index of T-AOC and stimulated glucose uptake in a concentration-dependent manner. Importantly, we successfully constructed a GDM mouse model through HFD. The treatment of chemerin was found to alleviate the high blood glucose levels in these HFD-fed pregnant mice and attenuate the excessive growth of their offspring. Our data also revealed that chemerin might counteract placental oxidative stress in HFD mice by improving the activity of superoxide dismutase. Conclusions The present study further elucidated the molecular biology of chemerin, which plays a pivotal role in ameliorating oxidative stress and hyperglycemia, resulting in improved fetal overgrowth in GDM. Graphical abstract